Investment portfolio optimization using evolutionary strategies - Wang, Yannan. (2011)
In the financial market, investors enter the market with the aim to make a profit. To ensure that they make an attractive investment, they carefully assess each asset’s performance and compare their risks and returns. When deciding on an investment, it is highly desirable to maximize the return while minimizing the risk level to a certain acceptable level. As the demand for this rises, portfolio optimization becomes a topic of great interest and importance to investors and financial institutions.